2013
DOI: 10.1371/journal.pmed.1001373
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Women Not Use Antenatal Services in Low- and Middle-Income Countries? A Meta-Synthesis of Qualitative Studies

Abstract: In a synthesis of 21 qualitative studies representing the views of more than 1,230 women from 15 countries, Kenneth Finlayson and Soo Downe examine the reasons why many women in low- and middle-income countries do not receive adequate antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
349
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(396 citation statements)
references
References 65 publications
41
349
2
4
Order By: Relevance
“…Numerous barriers to accessing care have been identified, including transportation [10], household commitments [11], under-resourced clinics with excessive waiting lines [11], and a lack of perceived benefit [12], in addition to delayed booking at clinics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous barriers to accessing care have been identified, including transportation [10], household commitments [11], under-resourced clinics with excessive waiting lines [11], and a lack of perceived benefit [12], in addition to delayed booking at clinics [13].…”
Section: Introductionmentioning
confidence: 99%
“…In regards to medical cost, the Government of Indonesia has launched the Health Insurance Scheme for the Population particularly poor communities in order to provide them with free access to health services [9]. However, financial difficulties associated with indirect costs of seeking antenatal care such as transportation costs are still significant barriers for pregnant women with lower family incomes to using antenatal care services [10]. This situation has been the main problem among women living in rural areas because the costs of transportation to health care services are very expensive [8,11].…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…Similarly, women who are better educated than their husbands are able to assert their own preferences and make their own decision to use antenatal care services [12]. In contrast, a study by Finlayson and Down [10] suggests that the decision to utilise antenatal care especially in some communities with hierarchical cultures is primarily made by husbands, mothers-in-law, or senior family members rather than the women themselves. Another study by Agus and Horiuchi [7] has also reported that women who take advices from their family to use or not to use antenatal care are simply because they want to satisfy their family.…”
Section: Archivos De Medicina Issn 1698-9465mentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors that negatively affect their motivation to seek ANC include extreme poverty and having a previous bad experience of ANC, which may have been inadequately provided 11 . A systematic review concerning utilization of ANC in developing countries identified several factors as affecting ANC attendance, such as maternal educational status, partner's educational status, marital status, availability and affordability of health care services, household income, etc 12 .…”
mentioning
confidence: 99%